Duas Escolas, uma lição: a Sociologia como instrumento de desracialização da Escola de Atlanta (1897-1910) e do Teatro Experimental do Negro (1948-1955)1 - Silva, Nikolas Pallisser; Santos, Hasani Eliotério Dos; Caldas, Alan [UNESP] (Associação Nacional de Pós-Graduação e Pesquisa em Ciências Sociais - ANPOCS, 2023)
The objective of this paper is to relate the idea of sociology as a weapon of liberation, developed among American scholars of the Atlanta School at the beginning of the twentieth century, and the conception of sociology as knowledge of salvation that emerged among intellectuals of the Teatro Experimental do Negro (TEN), specifically between 1948 and 1955. Our methodology consists of the historical reconstruction of the contexts and theories, comparing the similarities and differences in the appropriation of sociology by racialized intellectual communities in the United States and Brazil. We indicate how the Atlanta School (1897-1910) used Sociology to demonstrate that inequalities were the result of social and economic mechanisms, and not of alleged atavistic inferiority. TEN, on the other hand, resorted to Sociology, first as a means of constructing a project for the social integration of the black population, and then as a tool to unmask the ideologies produced by the Social Sciences. Thus, on the one hand, these two institutions worked against domination and exploitation based on racial categories; and, on the other, they constructed new forms of rationality oriented by emancipatory purposes.

O objetivo deste trabalho consiste em relacionar a concepção de sociologia como arma de libertação, desenvolvida entre acadêmicos(as) norte-americanos(as) da Escola de Atlanta, no início do século XX, e a concepção da sociologia como saber de salvação que emergiu entre os intelectuais do Teatro Experimental do Negro (TEN), especificamente entre 1948 e 1955. A metodologia consiste na reconstrução histórica dos contextos e teorias acima mencionados, cotejando os aspectos semelhantes e as diferenças de apropriação da sociologia pelas comunidades de intelectuais racializados nos Estados Unidos e no Brasil. Indicamos como a Escola de Atlanta (1897-1910) usou a Sociologia para demonstrar que as desigualdades eram resultado de mecanismos sociais e econômicos, e não de uma pretensa inferioridade atávica. Já o TEN recorreu à Sociologia primeiramente como meio de construção de um projeto de integração social da população negra, depois como ferramenta de desmascaramento das ideologias produzidas pelas Ciências Sociais. Assim, por um lado, as duas instituições trabalharam contra a dominação e a exploração feitas a partir da fixação de categorias raciais; e, por outro lado, construíram novas formas de racionalidade orientadas por propósitos emancipadores.
Two Schools, one lesson: Sociology as an instrument of deracialization of the Atlanta School (1897-1910) and the Teatro Experimental do Negro (1948-1955)
Keywords: W.E.B. Du Bois; Alberto Guerreiro Ramos; Atlanta Sociological School; Teatro Experimental do Negro; deracialization; W. E. B. Du Bois; Alberto Guerreiro Ramos; Escola de Atlanta; Teatro Experimental do Negro; desracialização